In pursuit of happiness: A sociological examination of employee identifications amongst a 'happy' call-centre workforce. (November 2014) - Jenkins, Sarah; Delbridge, Rick
While psychologists and economists have concerned themselves with employee happiness and well-being, critical organizational theorists have rarely examined employees' positive responses at work. To explain why call-centre employees in our study responded positively to their organization we adopt a relational sociological approach to examine employee happiness and well-being. This approach emphasizes two main features: firstly, it is sensitive to the interaction of management practices and employee agency in how 'happiness' is constructed and interpreted in organizations, including an assessment of power relations; secondly, this approach acknowledges the importance of the wider external context in explanations of why organizations pursue happiness. This article applies these sociological insights to the organizational identifications literature to assess the mechanisms of employee identifications. In this case, there are three mechanisms of identification, a) the organizational value system; b) social relations at work including interactions between employees, the owners and their clients and c) the nature of work. Significantly, these three features converged to produce overlapping and mutually reinforcing identifications.